Ultrasound-assisted extraction of phenolic compounds from coconut endocarp and its radical scavenging activity - siramon, pornpun; Wongsheree, Thitima; Yuadyong, Sarapee (Health Science, Science and Technology Reviews, 2020)
Phenolic compounds were extracted from the coconut endocarp waste, a by-product of the processing of coconut fruits. The optimum conditions for extraction of phenolic compounds from coconut endocarp using ultrasound-assisted extraction (UAE) were determined using three main parameters: solvent type, extraction temperature and extraction time. It was found that the extraction of sample with 50% (aq) of ethanol at 50 ºC for 120 minutes provided the highest crude extract yield (29.46% w/w on dry basis) and the highest total phenolic content (962.31 µg GAE/g). The antioxidant activity of crude ethanolic extract under the optimum condition was further investigated and the results showed that the crude extract exhibited strong antioxidant activity with IC50 values of 288.17 µg/ml by DPPH assay and 10.55 µg/ml by ABTS assay, respectively